TUNGAU DEBU RUMAH DI AREA KAMPUS UNIVERSITAS GADJAH MADA, DAERAH ISTIMEWA YOGYAKARTA - Pramestri Winda Windaswari (Bioma, 2019)
House Dust Mites (HDM) is an aeroallergen that can be found in various parts of urban homes such as mattresses, windows, and office furniture. HDM is a member of Order of Acarina which plays important role in the medical field as the main trigger of allergic reactions of people with asthma, rhinitis, conjunctivitis, and atopic dermatitis. The purpose of this study was to study the type, density, and factor which affecting of HDM populations in the campus area of Gadjah Mada University. This research was conducted in January-February 2018. Dust sampling at 8 Faculty and 2 Vocatioal School of Gadjah Mada University in Yogyakarta. Taken 3 point of dust sample in each location by using vacuum cleaner and was put in transparent plastic bag (ziplock) and inserted in the Tullgreen Tornado. Preparation HDM that has been observed using light microscope and identified using the Krantz Key (1978). The results obtained 7 genus with abundance respectively Cheyletus (16.40%), Tyrophagus (9.29%), Glycyphagus (40.44%), Carpoglyphus (6.55%), Tarsonemus (4.92%), Acarus (14.75%), and Blomia (7.65 %). Temperature, humidity, and feeding factors have an effect on increasing the growth and development of HDM populations. Keywords: house dust mites, type, abundance, density, the campus of UGM